2010
DOI: 10.1186/1532-429x-12-70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gadolinium contrast agent on aortic blood flow and myocardial strain measurements by phase-contrast cardiovascular magnetic resonance

Abstract: BackgroundQuantitative blood flow and aspects of regional myocardial function such as myocardial displacement and strain can be measured using phase-contrast cardiovascular magnetic resonance (PC-CMR). Since a gadolinium-based contrast agent is often used to measure myocardial infarct size, we sought to determine whether the contrast agent affects measurements of aortic flow and myocardial displacement and strain. Phase-contrast data pre and post contrast agent was acquired during free breathing using 1.5T PC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…3335 Despite these findings, previous studies have found no significant difference in absolute flow quantification, a finding in contradistinction to our own finding of a slight increase in aortic flow post-contrast administration. 14 The differences in aortic flow quantification, however, were small amounting to only a 2 ml (2.5%) difference before and after contrast administration. Conversely, SA analysis resulted in no such difference.…”
Section: Discussionmentioning
confidence: 95%
“…3335 Despite these findings, previous studies have found no significant difference in absolute flow quantification, a finding in contradistinction to our own finding of a slight increase in aortic flow post-contrast administration. 14 The differences in aortic flow quantification, however, were small amounting to only a 2 ml (2.5%) difference before and after contrast administration. Conversely, SA analysis resulted in no such difference.…”
Section: Discussionmentioning
confidence: 95%
“…4D‐flow data in patients were assessed after contrast agent, whereas no contrast agent was applied in healthy controls. Even though they affect the SNR of the data, measured velocities and velocity fields should not be affected by contrast agent 7,42,43 …”
Section: Discussionmentioning
confidence: 99%
“…Even though they affect the SNR of the data, measured velocities and velocity fields should not be affected by contrast agent. 7,42,43 Manual segmentation was performed with prototype software that is optimized for 4D-flow data preprocessing and visualization rather than segmentation, which explains the long manual segmentation times per subject. Segmentation time might be substantially decreased with suitable 4D-flow data segmentation software.…”
Section: Limitationsmentioning
confidence: 99%
“…The presence or absence of gadolinium contrast agent in the blood had no demonstrable effect on phase contrast measurements of aortic flow in this study[ 30 ]. Therefore, when assessing blood flow as well as myocardial viability, time may be saved by measuring flow after gadolinium injection and before the acquisition of late gadolinium enhancement images.…”
Section: Flow Evaluation and Valve Diseasementioning
confidence: 93%